Effect of domestic COVID-19 vaccine on the plasma D-dimer levels of early pregnant women in China - Liang, Wenjuan; Fu, Xin; Li, Rui; Yang, Liu; Liu, Peng; Guo, Xuan; Jia, Qinliang; Wang, Ziran; Xie, Yun (Frontiers in Medicine, 2023)
Objective To investigate the effect of COVID-19 vaccination on plasma D-dimer levels in early pregnant women. Methods A total of 834 early pregnant women(gestational age ≤ 13 weeks), who visited Northwest Women and Children’s Hospital between December 2020 and April 2022, were selected. There were 696 women in the healthy group (group A) and 138 in the group with a history of adverse pregnancy and childbirth (group B). The plasma D-dimer levels of all participants were tested, and the COVID-19 vaccine history of all participants was collected using a survey questionnaire. Results The plasma D-dimer levels did not differ between group A and the group B (p = 0.1327). In the group A, 470 were vaccinated and 226 were unvaccinated. The D-dimer levels of vaccinated individuals were lower than those of unvaccinated individuals (p = 0.0047). In the group B, 84 were vaccinated and 54 were unvaccinated; no difference in D-dimer levels was found between the vaccinated and unvaccinated individuals (p = 0.0542). In the group A, the D-dimer levels of the unvaccinated group were not different from those of women vaccinated with one dose (p = 0.208), but they were higher than those who received two doses (p = 0.019) or three doses (p = 0.003). And, no significant difference in D-dimer levels was found among women who received different vaccine brands and with different vaccination times. Conclusion This study preliminarily indicates that COVID-19 vaccination does not increase D-dimer levels in early pregnant women.